Impact of reggaeton and modern music on adolescent sexual behavior: Bibliometric analysis and literature review - Morillo Cano , Julio Rodrigo; Guepud Guapaz , Anderson Ramiro; Castro Moscoso , Nathaly Paola; Morillo Chamorro , María Belén (Salud, Ciencia y Tecnología - Serie de Conferencias, 2024)
The research examines the impact of modern music, particularly reggaeton, on adolescent sexual behavior. Music, as a form of expression and communication, has historically influenced people’s emotions and behaviors. In the contemporary context, exposure to explicit lyrics and musical content has raised concerns about its influence on youth sexuality. This study’s literature review and bibliometric analysis focused on articles published in databases such as Scopus, Web of Science, and PubMed, among others. A total of 42 relevant references were identified, with 15 selected for a more detailed review based on specific inclusion and exclusion criteria. The results show a growing trend in research on reggaeton and its influence on adolescent sexuality. Studies reveal that exposure to explicit sexual lyrics and objectification in music videos is associated with increased sexual activity and permissive attitudes toward sex among youth. Reggaeton, in particular, is noted for reinforcing gender stereotypes and promoting a hypersexualized view of relationships, contributing to the normalization of risky sexual behaviors. The research suggests that increased awareness and education can help mitigate negative influences and promote healthier sexual behaviors among young people